Retrospective study of chemotherapy induced cardiotoxicity from a tertiary cancer centre in South India - Nandennavar, Manjunath I.; Sekar, Annalakshmi; Karpurmath, Shashidhar V. (International Journal of Research in Medical Sciences, 2016)
Background: Ever increasing therapeutic modalities in treatment of various malignancies has resulted in an enormous number of cancer survivors. Cancer survivors face various issues in their long term health due to the cancer and/or its treatment. Late effects including organ damage, functional disability and risk of second malignancy continue to be elucidated. One of the most debilitating and serious toxicity is cardiotoxicity due to chemotherapy. Methods: This study was a retrospective analysis of all patients who developed chemotherapy induced cardiotoxicity between January 2013 to December 2015. Results: A total of 16 patients developed cardiotoxicity. 13 patients had doxorubicin induced toxicity. Cardiotoxicity was noted to occur at low cumulative doses. 2 patients had complete recovery of left ventricular ejection fraction (LVEF) on follow up. 1 patient had progressive worsening of LVEF. 1 patient died due to cardiotoxicity. On detection of cardiotoxicity, most of the patients received cardiac remodeling drugs - angiotensin converting enzyme inhibitors (mostly enalapril), other drugs used were carvedilol and diuretics. Conclusions: In Indian patients, cardiotoxicity can occur at very low cumulative doses of doxorubicin and in young patients too. Most of the patients did not have any underlying comorbid illnesses. We wish to highlight the need to diligently repeat cardiac screening investigations at frequent intervals to detect asymptomatic cardiotoxicity.